Thymidine Kinase-Negative Herpes Simplex Virus 1 Can Efficiently Establish Persistent Infection in Neural Tissues of Nude Mice - Huang, Chih-Yu (J Virol, 2017)
Herpes simplex virus 1 (HSV-1) establishes latency in neural tissues of immunocompetent mice but persists in both peripheral and neural tissues of lymphocyte-deficient mice. Thymidine kinase (TK) is believed to be essential for HSV-1 to persist in neural tissues of immunocompromised mice, because infectious virus of a mutant with defects in both TK and UL24 is detected only in peripheral tissues, but not in neural tissues, of severe combined immunodeficiency mice (T. Valyi-Nagy, R. M. Gesser, B. Raengsakulrach, S. L. Deshmane, B. P. Randazzo, A. J. Dillner, and N. W. Fraser, Virology 199:484–490, 1994, https://doi.org/10.1006/viro.1994.1150). Here we find infiltration of CD4 and CD8 T cells in peripheral and neural tissues of mice infected with a TK-negative mutant. We therefore investigated the significance of viral TK and host T cells for HSV-1 to persist in neural tissues using three genetically engineered mutants with defects in only TK or in both TK and UL24 and two strains of nude mice. Surprisingly, all three mutants establish persistent infection in up to 100% of brain stems and 93% of trigeminal ganglia of adult nude mice at 28 days postinfection, as measured by the recovery of infectious virus. Thus, in mouse neural tissues, host T cells block persistent HSV-1 infection, and viral TK is dispensable for the virus to establish persistent infection. Furthermore, we found 30- to 200-fold more virus in neural tissues than in the eye and detected glycoprotein C, a true late viral antigen, in brainstem neurons of nude mice persistently infected with the TK-negative mutant, suggesting that adult mouse neurons can support the replication of TK-negative HSV-1. IMPORTANCE Acyclovir is used to treat herpes simplex virus 1 (HSV-1)-infected immunocompromised patients, but treatment is hindered by the emergence of drug-resistant viruses, mostly those with mutations in viral thymidine kinase (TK), which activates acyclovir. TK mutants are detected in brains of immunocompromised patients with persistent infection. However, answers to the questions as to whether TK-negative (TK(−)) HSV-1 can establish persistent infection in brains of immunocompromised hosts and whether neurons in vivo are permissive for TK(−) HSV-1 remain elusive. Using three genetically engineered HSV-1 TK(−) mutants and two strains of nude mice deficient in T cells, we found that all three HSV-1 TK(−) mutants can efficiently establish persistent infection in the brain stem and trigeminal ganglion and detected glycoprotein C, a true late viral antigen, in brainstem neurons. Our study provides evidence that TK(−) HSV-1 can persist in neural tissues and replicate in brain neurons of immunocompromised hosts.